Characterization of white spot lesions formed on human enamel under microcosm biofilm for different experimental periods - Flávia Mauad Levy; Aline Silva Braga; Vinícius Taioqui Pelá; Stacey Lavender; Dennis Zhang; Shira Pilch; Zilson Malheiros; Bernal Stewart; Ana Carolina Magalhães; Marília Afonso Rabelo Buzalaf (University of São Paulo, 2022)
Abstract The initial characteristics of white spot lesion (WSLs), such as the degree of integrated mineral loss (ΔZ), depth and pattern of mineral distribution, have an impact on further demineralization and remineralization. However, these lesion parameters have not been evaluated in WSLs produced from microcosm biofilms. Objective: This study characterized artificial white spot lesions produced on human enamel under microcosm biofilm for different experimental periods. Methodology: In total, 100 human enamel specimens (4x4mm) were assigned to 5 distinct groups (n=20/group) differing according to the period of biofilm formation (2, 4, 6, 8 or 10 days). Microcosm biofilm was produced on the specimens from a mixture of human and McBain saliva at the first 8h. Enamel samples were then exposed to McBain saliva containing 0.2% sucrose. WSLs formed were characterized by quantitative light-induced fluorescence (QLF) and transverse microradiography (TMR). Data were analyzed by ANOVA/Tukey or Kruskal-Wallis/Dunn tests (p<0.05). Results: A clear time-response pattern was observed for both analyses, but TMR was able to better discriminate among the lesions. Regarding QLF analysis, median (95%CI; %) changes in fluorescence ∆Z were -7.74(-7.74:-6.45)a, -8.52(-8.75:-8.00)ab, -9.17(-10.00:-8.71)bc, -9.58(-10.53:-8.99)bc and -10.01(-11.44:-9.72)c for 2, 4, 6, 8, and 10 days, respectively. For TMR, median (95%CI; vol%.µm) ∆Z were 1410(1299-1479)a, 2420(2327-2604)ab, 2775(2573-2899)bc, 3305(3192-3406)cd and 4330(3972-4465)d, whereas mean (SD; µm) lesion depth were 53.7(12.3)a, 71.4(12.0)a, 103.8(24.8)b, 130.5(27.2)bc, 167.2(39.3)c for 2, 4, 6, 8 and 10 days, respectively. Conclusion: The progression of WSLs formed on human enamel under microcosm biofilm can be characterized over 2-10 days, both by QLF and TMR analyses, although the latter provides better discrimination among the lesions.